Preliminary observations on the milk production of Borana cattle in the southern rangeland - Dessalegne, B. (1982)
A preliminary observational study was conducted to determine milk production levels and milk compositions characteristics of free-range Boran cattle and to examine variations. Results obtained using 19 Borana Cows indicate; milk yield per off take was 487.5 kg (Range: 319.9-691.6 kg) with an average lactations period of 249.2 days. Average daily productions per lactations was 2.02 kg. The mean butterfat, protein, S.N.F., total solids, ash and lactose contents of 159 milk samples analyesd were found to be 4.9±1.62, 3.3±0.5, 9.2±1.09, 14.12±1.87, 0.8±0.18 and 4.9±1.11% respectively.